مقدمہ اوجز المسالک الی مؤطاامام مالک ؒ میں شیخ زکریاؒ کامنہج واسلوب: Methodology of sheikh Zakaria in the preface of Awjaz-ul-Masalik Ila Muatta Imam-i-Malik - Dr Muhammad Inamullah; Muhammad Sanaullah; Muhammad Waliaullah (Al Manhal Research Journal, 2023)
Methodology of sheikh Zakaria in the preface of Awjaz-ul-Masalik Ila Muatta Imam-i-Malik. Muatta Imam-i-Malik is a famous and authentic collection of Ahadith edited by Imam Malik (93-179 AH), known as a founder of a juristic school of thought. It is the first comprehensive book containing Islamic Teachings after the Holy Quran. Due to its authenticity & popularity among academic circle , various books have been written for its explanation and clarification. Among them “Awjaz-ul-Masalik” is a latest and comprehensive elucidation comprising 16 volumes , edited by a great indian scholar Sheikh-ul- Hadith Maulana Zakaria Kandehlawi. It is a summary of almost all the previous commentaries edited by renowned scholars of Hadith. Due to quality of work the work has already acknowledged by the contemporary Arab scholars as well. The author has presented detailed preface containing 7 chapters and 150 pages which cover various aspects of Hadith , including the status of Imam Abu Hanifa as a scholar of Hadith, his principles of Hadith and various observations and clarifications regarding his competence in the subject. Due to its valuable material this preface needs to be explored. This article aims at introducing the contents and evaluation of work presented in this preface.